Pediatric anaphylactic adverse events following immunization in Victoria, Australia from 2007 to 2013. Issue 13 (24th March 2015) - Cheng, Daryl R.; Perrett, Kirsten P.; Choo, Sharon; Danchin, Margie; Buttery, Jim P.; Crawford, Nigel W.
Highlights: Anaphylaxis as an adverse event following immunization (AEFI) is a rare but important diagnosis. This is due to associated morbidity risk and implications for future vaccinations. Diagnostic criteria for anaphylaxis are difficult to implement in a passive AEFI surveillance system. All cases of anaphylaxis in this Australian case series had no long-term sequelae. Abstract: Background: Anaphylaxis is a rare life-threatening adverse event following immunization (AEFI). Variability in presentation can make differentiation between anaphylaxis and other AEFI difficult. This study summarizes pediatric anaphylaxis AEFI reported to an Australian state-based passive surveillance system. Methods: All suspected and reported pediatric (<18 years) anaphylaxis AEFI notified to SAEFVIC (Surveillance of Adverse Events Following Vaccination In the Community) Melbourne, Australia, between May 2007 to May 2013 were analyzed. Clinical descriptions of the AEFI, using the internationally recognized Brighton Collaboration case definition (BCCD) and final outcome were documented. Results: 93% (25/27) of AEFI classified as anaphylaxis met BCCD criteria, with 36% (9/25), assessed as the highest level of diagnostic certainty (Level 1). Median age was 4.7 years (range 0.3–16.2); 48% of cases were male. The vaccine antigens administered included: diphtheria, tetanus, acellular pertussis (DTaP) alone or in combination vaccines containing other antigens in 11 of 25 cases (44%); and live attenuated measles mumps rubella (MMR) vaccine for six (five also had other vaccines concomitantly administered). The estimated incidence rate of anaphylaxis for DTaP vaccines was 0.36 cases per 100, 000 doses, and 1.25 per 100, 000 doses for MMR vaccines. The majority of cases had rapid onset, but in 24% (6/25) of cases, first symptoms of anaphylaxis developed ≥30 min after immunization. In 60% (15/25) of cases, symptoms resolved ≤60 min of presentation. Intramuscular adrenaline was administered in 90% (18/25) of cases. All cases made a full recovery with no sequelae identified. Conclusion: This comprehensive case series of pediatric anaphylaxis as an AEFI identified that diagnostic criteria are useful when applied to a passive vaccine surveillance system when adequate clinical information is available. Anaphylaxis as an AEFI is rare and usually begins within 30 min of vaccination. However, healthcare professionals and vaccinees/parents should be aware that onset of anaphylaxis can be delayed beyond 30 min following immunization and that medical attention should be sought promptly if anaphylaxis is suspected.